The Participation of Street Food Sellers in Formulating the Policy of Revitalizing the Tegal’s Town Square Area as the Effort to Improve the Opened Green Zone - Rosyida, Melina; Setiyono, Budi; Kushandajani, Kushandajani (Lenggogeni Data Publishing, 2024)
This research determined the participation of street food sellers in formulating and issuing the policy and determined the hindering factors of revitalization policy in the town square area of Tegal as the effort to improve the opened green zone. This descriptive qualitative research describes a variable in the form of spoken data from the informants and the observed behaviors of the informants. The researchers collected the data by interviewing the civil service police officers, the public work service and spatial planning, the cooperation of SME and trading, the housing and residential department, and the association of street food sellers; documenting; and studying the works of literature. The results found many regional government organizations participated in the formulation of revitalization policy. Then, they took the responsibility directly to the major of Tegal as the policy- maker of revitalizing the town square area of Tegal. The revitalization ran successfully. The government socialized the policy systematically and involved various actors including the street food sellers. However, from the eight socialization stage meetings for the street food sellers, only three socialization stages involved and coordinated with the street food sellers. The three meetings shared the divisions and relocation sites of the sellers, instruction, and empowerment. The revitalization of the green town square area also encountered some hindrances, such as limited socialization, lack of street seller confidence, and less representative relocated sites.